ADJEKTIVA BAHASA BALI - I Wayan Budiarta (SPHOTA: Jurnal Linguistik dan Sastra, 2014)
ABSTRACT The titile of this paper is Balinese adjective. This paper tries to describe the uniqneness of the grammatical behavior/characteristic of adjective in Balinese. This phenomenon is interested to be analysed due to adjective that has grammatical characterictic like other word class, such as verb and noun. The theory applied in this study is taken from Dixon (2010) entitled Basic Grammatical Theory. Data source of this research is oral data which is taken from the native speaker of Balinese. There are five respondents which are choosen in this research. More over, the data source of this research is collected through interview and observation methods.The result of data analysis shows that adjective in Balinese can be put together with noun to form noun phrase in which the function of adjective is as modifier. There are six affixes which cause the change in grammatical characteristic of adjective. Those affixes are: (1) suffix –ang, (2) combination of suffixes –ang and –a, (3) suffix –in, (4) combination of suffixes –in and –a, (5) suffix –an, and (6) confixes ng-ang. The marker of aspect, tense, mood can be attached to adjective in Balinese, and adjective is the only word class that can take the comparative structure. Keywords: Adjective, Balinese, grammatical behavior, modifier